Vatican’s media strategy on war in Ukraine - Zavadilová, Tereza (Kultura Media Teologia, 2024)
Since the beginning of the Russian offensive in Ukraine on 24th February 2022, the Vatican media were busy making known the distress of the Ukrainian people, whereas the Pope and the Secretariat of State seemed to be taking a more general position, to maintain contacts with Moscow and to keep the door open to mediation. In general, Vatican media controlled by the Dicastery for Communication have published numerous articles on the topic, very clearly denouncing Russia’s responsibility. In comparison to this consistent approach, some of Pope’s statements – apparently not very well prepared in terms of strategic institutional communication – fell under public scrutiny. Nevertheless, Pope oft labelled the aggression a “sacrilege” and appealed for an end to the violence and long-term welcome of Ukrainian refugees. This contribution sums up the year-long (24th February, 2022 – 24th February, 2023) Vatican media communication on the topic of this war. The combination of quantitative and qualitative content analysis of the English version of the Vatican News website production is used to show the tendencies in the context of overall strategic institutional communication of the Holy See. The topic is also seen from the point of the non-corporate (independent) Catholic journalism limited to America Magazine, La Croix, Avvenire, and The Tablet.